Identification of Four Immune Subtypes in Bladder Cancer Based on Immune Gene Sets - Tang, Chaozhi; Ma, Jiakang; Liu, Xiuli; Liu, Zhengchun (Frontiers in Oncology, 2020)
The molecular classification of bladder cancer is becoming increasingly important for its clinical management, however, it is largely based on gene expression profiles. We identified four immunotypes of bladder cancer (referred to as C1–C4) based on immune-related gene sets in three independent data sets and proved that this classification is effective and repeatable. We found that C2 is an immune-infiltrating type and C4 is an immune desert type. These types are characterized by the up- and downregulation of genes encoding numerous immune checkpoints, HLA, and human immune cell subgroups, respectively. The survival rate was better for the C2 subtype than for other subtypes. We believe that this can be explained by the antitumor effects of CD4 memory T cells and CD8 T cells as well as the ability to circumvent M0 macrophage antitumor-immunity. We further identified tumor-related JAK–STAT and other signaling pathways in the C2 subtype, revealing the complex mechanism underlying tumor escape. Our results, and particularly the identification of hub genes specific to the C2 and C4 subtypes, provide a reference for the development of immunotherapeutic agents.